2008
DOI: 10.1017/s0967199407004455
|View full text |Cite
|
Sign up to set email alerts
|

Global poly(A) mRNA expression profile measured in individual bovine oocytes and cleavage embryos

Abstract: The objective of this article was to estimate quantitative differences for GAPDH transcripts and poly(A) mRNA: (i) between oocytes collected from cumulus-oocyte complexes (COCs) qualified morphologically as grades A and B; (ii) between grade A oocytes before and after in vitro maturation (IVM); and (iii) among in vitro-produced embryos at different developmental stages. To achieve this objective a new approach was developed to estimate differences between poly(A) mRNA when using small samples. The approach con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 61 publications
0
19
0
5
Order By: Relevance
“…During the growth phase cattle oocytes synthesize a large amount of mRNA, this can be seen from the secondary follicle and is maintained up to the tertiary follicle (136,137) . In other words, in the bovine system transcription of mRNA begins to decline when the oocyte completes its growth and reactive meiosis II towards metaphase II (138) .…”
Section: Maternal Mrna In the Bovinementioning
confidence: 99%
See 4 more Smart Citations
“…During the growth phase cattle oocytes synthesize a large amount of mRNA, this can be seen from the secondary follicle and is maintained up to the tertiary follicle (136,137) . In other words, in the bovine system transcription of mRNA begins to decline when the oocyte completes its growth and reactive meiosis II towards metaphase II (138) .…”
Section: Maternal Mrna In the Bovinementioning
confidence: 99%
“…Likewise, this process is mediated by the deadenylation of the extreme 3´UTR of the mRNA, through the action of proteins such as CPEB and eIF4G (139) . It has been shown that mature oocytes present mRNA with tails of polyadenin shorter than in those immature oocytes; however these mRNA with long tails of adenines, after fertilization in the stadium of 2 cells are deleted (137) . In cattle maternal mRNA storage during oogenesis is necessary to carry out a proper embryonic development (137) .…”
Section: Maternal Mrna In the Bovinementioning
confidence: 99%
See 3 more Smart Citations